2000
DOI: 10.1023/a:1004115432660
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our objective was to determine whether subarachnoid haemorrhage modifies cerebral artery smooth muscle cell phenotype and the contractile protein alpha-actin measured 7 days after haemorrhage. We used a rabbit subarachnoid haemorrhage model and immunofluorescence labelling of alpha-smooth muscle actin, vimentin and desmin. The paired comparison between the haemorrhage and sham rabbits was performed using confocal laser-scanning microscopy. We found in the haemorrhage group significantly less intense alpha-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This type of denervation could be expected to result in loss of neurogenic control of cerebral arteries [55] and impairment of autoregulation. In the media, myonecrosis occurs with loss of contractile protein in the smooth muscle [58, 59]; additionally, the amount of interstitial collagen increases [58]. Together these processes contribute to arterial narrowing which is not vasospasm-mediated [60].…”
Section: Introductionmentioning
confidence: 99%
“…This type of denervation could be expected to result in loss of neurogenic control of cerebral arteries [55] and impairment of autoregulation. In the media, myonecrosis occurs with loss of contractile protein in the smooth muscle [58, 59]; additionally, the amount of interstitial collagen increases [58]. Together these processes contribute to arterial narrowing which is not vasospasm-mediated [60].…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1997, however, evidence began to accumulate indicating that the blood-brain barrier, and possibly small arteries, were also injured by ICH (4). Further evidence demonstrated that intracerebral blood could alter cytoskeletal organization within cerebral arteries (17) and even induce contractile dedifferentiation (36). Current evidence strongly implies that phenotypic transformation of cerebrovascular smooth muscle and altered contractile function are prominent consequences of ICH (42,52), although the mechanisms mediating this vascular injury remain unclear.…”
mentioning
confidence: 99%
“…Vascular remodeling after SAH, as well as cellular growth, could be mainly attributed to increased beta-actin mRNA expression [ 543 ]. The decreased alpha-actin intensity in VSMC probably contributes to the VSMC shift towards a more synthetic (less differentiated) phenotype [ 544 ].…”
Section: Reaction To Sah Of Neurovascular Unit Cellsmentioning
confidence: 99%